Editorial: Signs of EFL resistance to critical times - Bonilla Medina, Ximena; Quintero Polo, Álvaro Hernán (Colombian Applied Linguistics Journal, 2021)
We have been living hard times since 2020 when a health emergency initiated with the COVID-19 pandemic. All around the globe, teachers and students have faced changes that have transformed not only academic procedures but also social life. In this vein, we have also seen how the authors that have collaborated sending their papers to the journal have made an effort to shed light on how, either academic or social practices, have been featured to continue their compromise to educate in the pursue a better world despite the circumstances. Some of these approaches are part of this number and others will be part of the upcoming ones. Accordingly and, coinciding with Freire’s centenary, we want to acknowledge that the experiences shared in this journal constitute the evidence of how teachers, professors, researchers and educators in the field of applied linguistics maintain their commitment faithfully to their profession, work that is notoriously underpinned by a pedagogy of hope.